An experiment-based cohesive-frictional constitutive model for cemented materials. (September 2022) - Senanayake, S.M.C.U.; Haque, A.; Bui, H.H.
Abstract: Experiment-based damage laws at the contact bond level are often absent in the computational modelling of cemented materials using cohesive contact-bond models. In this paper, in-situ X-Ray Computed Tomography on element-scale cement bonds subjected to pure compression, shear and tensile loading was conducted to investigate their failure mechanisms and associated damage laws. A new cohesive-frictional constitutive model was subsequently developed using results obtained from X-Ray CT tests. The new constitutive model was capable of describing the behaviour of contact bonds subjected to complex loading conditions, including mixed-mode and compression damage. The new model was then implemented in an open-access Discrete Element Code (YADE) to simulate several challenging laboratory-scale tests (e.g., triaxial, Brazilian and Splitting tests) and very good agreements with the experimental data were achieved.